(untitled) (EDUCATION IN THE 21ST CENTURY, 2024)
The development and socialization of a child involves the creation of pedagogical and social situations typical of age, which involves the organization of activities that contribute to the development of thinking. Visual-imaginative thinking of a child, where the main unit is an image, manifests itself at the age of 2-3 years and is a priority until 6-7 years old. Spatial thinking is formed as a result of the variety of pictorial thinking. the child operates with spatial images based on the creation of these images through the perception (or representation) of spatial properties and relationships between objects. The study of the development of spatial thinking in preschool children was conducted by such scientists as J.S. Grigorieva, A.N. Davidchuk, T.S. Komarova, L.V. Kutsakova, L. A. Paramonova, N.P. Sakulina, N.F. Tarlovskaya and many others. Spatial thinking is the foundation on which most of human activity is based, so its development and formation are an important part of the successful formation of a child’s personality later in life. In the structure of the human psyche, it is responsible for orientation in space, creating images of space in the human mind and using them in the process of solving various problems. During our study, we identified the role of mirror neurons in the performance of higher integration functions of the brain. The formation of spatial orientation in children of early and preschool age with developmental disabilities is effectively carried out on the basis of developing, correcting and stimulating work of motor and speech activity. Attention should be paid to the use of complementary teaching methods, giving priority to the development and correction of motor skills.